PREVALENSI KOKSIDIOSIS PADA PEDET DI KABUPATEN KARANGANYAR - , ZULFIYAH DEVA ISTIYANI; , Prof. Em. Setyawan Budiharta MPH. Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Coccidiosis is a disease of farm animal caused by Coccidia. The presence of this disease causes economic losses to the farmers. The objectives of this study were to reveal the prevalence and factors associated with coccidiosis infection in calves in the district of Karanganyar. This study was a part of the larger cross-sectional study on the epidemiology of parasitic diseases in calves in Central Java using fecal samples of 1171 beef calves. In the district of Karanganyar, 140 beef calve sample used were selected from four subdistricts consisting of 10 villages randomly and proportionally. Each sample was identified with the district, subdistrict, and village codes, the number of farmer sample. Samples were taken to the laboratory to be examined of the presence of coccidia oocyst using floatation method. A calf was designated as suffering from coccidiosis if there was an oocyst in feces. Variables examined included those of the farmer, calves, breeding management, and environment. Every variable was described its association with coccidiosis was calculated using Ï2 test and odds ratio for its strength. The results showed the prevalance of coccidiosis in the district of Karanganyar was found to be 38,70 %. The only variable that associated with coccidiosis is liquid fecal. It was concluded that the farming condition of farmers in the district was relatively homogenous. The goverment is suggested to give more intensive extension on farm animal health.